2002
DOI: 10.1103/physrevb.66.085119
|View full text |Cite
|
Sign up to set email alerts
|

Local symmetry breaking in paramagnetic insulating(Al,V)2O3

Abstract: Evidence for short range orbital order in paramagnetic insulating (Al,V) The local structure of (Al0.06V0.94)2O3 in the paramagnetic insulating (PI) and antiferromagnetically ordered insulating (AFI) phase has been investigated using hard and soft x-ray absorption techniques. It is shown that: 1) on a local scale, the symmetry of the vanadium sites in both the PI and the AFI phase is the same; and 2) the vanadium 3d -oxygen 2p hybridization, as gauged by the oxygen 1s absorption edge, is the same for both ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…These insulating phases have a similar electronic structure. 39,41 A comparable modification of the spectral shape occurs for the bare V 2 O 3 ͑1120͒ layer at the PM-to-AFI phase transition ͑Fig. 7, left panel͒.…”
Section: B Microscopic Properties Of Fe Co and V In Fe"co… /V 2 O mentioning
confidence: 80%
“…These insulating phases have a similar electronic structure. 39,41 A comparable modification of the spectral shape occurs for the bare V 2 O 3 ͑1120͒ layer at the PM-to-AFI phase transition ͑Fig. 7, left panel͒.…”
Section: B Microscopic Properties Of Fe Co and V In Fe"co… /V 2 O mentioning
confidence: 80%
“…This procedure allows one to separate scattering paths along and perpendicular to the hexagonal c axis as detailed in Ref. 5.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the techniques using these x-ray spectroscopy methods to study local structure of materials can be found in Refs. [25][26][27][28][29][30][31][32]. XANES experiments ͑beamline X11A at NSLS͒ were mainly focused on the Ti K edge to examine its possible off-center displacement while the EXAFS data were collected for all three cations ͑K edge of Cu, Ti at beamline X11A and Ca at beamline X15B, NSLS͒ to measure the cation short-range order.…”
Section: B Synchrotron X-ray Diffractionmentioning
confidence: 99%